“I Have No Hope”: The Experience of Mothers in Polygamous Families as Manifested in Drawings and Narratives - Gadban, Faten; Goldner, Limor (Frontiers in Psychology, 2020)
Polygamy is associated with lower marital satisfaction and is known to involve sexual, physical, and emotional abuse on the part of the husband. Less is known about the experience of mothers in polygamous families. This study was designed to shed light on women's experiences in polygamous families in a sample of 80 Israeli Arab mothers living in polygamous families who use social services, domestic violence agencies, and health centers. Mothers were asked to draw their experiences in their families and to provide narratives to the drawings. The phenomenological approach was used to analyze the drawings, and yielded five different pictorial phenomena: 1) pseudo sweetness, 2) houses, 3) the absentee father and the estranged mother, 4) incorporation of graphic symbols and lettering that represented distress, 5) growth and development. Most of the drawings were restricted and shallow, indicating a complex emotional state of despair and distress. The central feelings that emerged from the drawings were negative emotions of anger, sadness, loneliness, and powerlessness. While some women longed for romantic relationships with their husbands, others expressed the desire for revenge and justice. Dissociation and parentification, as central coping strategies, emerged from the drawings and the narratives. The findings are discussed theoretically and clinically.